Acellular Dermal Matrix (Permacol®) for Heterologous Immediate Breast Reconstruction after Skin-Sparing Mastectomy in Patients with Breast Cancer: A Single-Institution Experience and a Review of the Literature - Knabben, Laura; Kanagalingam, Gowthami; Imboden, Sara; Günthert, Andreas R. (Frontiers in Medicine, 2017)
Objective: Skin-sparing mastectomy (SSM) with immediate heterologous reconstruction is a safe oncological option in surgical therapy of early breast cancer. Permacol® is an acellular dermal matrix (ADM) placed between the implant and the skin to improve lower pole projection and implant coverage. The aim of our study was to evaluate the outcome with a focus on patient satisfaction after six months and to analyze physical changes of ADM. Methods: 10 patients who underwent SSM with Permacol® were analyzed retrospectively. All patients were followed using a satisfaction questionnaire and an ultrasound evaluation of the tissue thickness of the pectoralis muscle and the Permacol®. Results: No intraoperative complications were observed. One patient required removal of the implant for necrosis after three months. Half of the patients underwent secondary corrective surgery. A statistically significant thinning of the pectoralis muscle was observed, compared to the thickening of the Permacol®. A majority of the patients were satisfied with the operation and we found a correlation between lower body mass index and patient satisfaction. Conclusion: In our small case series Permacol®-assisted immediate reconstruction is shown to be an option for selected cases. Physical changes of Permacol® result in a symmetrical coverage of the implant, which may improve cosmetic outcome.